1980
DOI: 10.1037/0022-006x.48.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Focused versus broad-spectrum behavior therapy for problem drinkers.

Abstract: The relative effectiveness of focused versus broad-spectrum approaches in teaching moderation to problem drinkers was evaluated. Of 56 clients randomly assigned to treatment conditions, 45 began treatment and 41 (21 men and 20 women) completed enough sessions to be regarded as treated in one of four groups: (a) bibliotherapy, in which clients received self-help materials but no treatment sessions, (b) behavioral self-control training (BSCT), consisting of six weekly sessions, (c) BSCT plus 12 sessions of relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
179
1
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(190 citation statements)
references
References 24 publications
7
179
1
3
Order By: Relevance
“…It is possible then that the empathic, reflective listening style adopted by MI therapists could at least partly explain MI's efficacy. Miller's group has conducted a number of studies suggesting that therapist empathy is directly related to treatment outcome (Miller & Baca, 1983;Miller, Benefield, & Tonigan, 1993;Miller, Taylor, & West, 1980). Another study indicated that general therapist interpersonal skill predicts patient engagement in MI sessions, even when therapists use specific techniques that are not consistent with MI (e.g., confronting patients) .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible then that the empathic, reflective listening style adopted by MI therapists could at least partly explain MI's efficacy. Miller's group has conducted a number of studies suggesting that therapist empathy is directly related to treatment outcome (Miller & Baca, 1983;Miller, Benefield, & Tonigan, 1993;Miller, Taylor, & West, 1980). Another study indicated that general therapist interpersonal skill predicts patient engagement in MI sessions, even when therapists use specific techniques that are not consistent with MI (e.g., confronting patients) .…”
Section: Discussionmentioning
confidence: 99%
“…Therapist warmth, empathy, and a positive relationship bond are most strongly associated with treatment outcome when the patient's perceptions of these qualities are considered (Lambert & Bergin, 1994;Orlinsky et al, 1994). Even in specific behavioral therapies, patients who view their therapist as warm and empathetic will be more involved in their treatment and ultimately, have a better outcome (e.g., Holtzworth-Munroe, Jacobson, DeKlyen, & Whisman, 1989;Miller, Taylor, & West, 1980;Williams & Chambless, 1990). According to Orlinsky et al (1994), these conclusions are based on literally hundreds of empirical results and can be considered scientific "facts" (p. 361).…”
Section: Research On the Treatment Relationshipmentioning
confidence: 99%
“…46 This uniformity suggests that common elements shared by all effective psychotherapies-including therapist empathy toward the patient and formation of a strong therapeutic alliance-have an impact on both compliance and positive outcomes. 47 A study involving problem drinkers conducted by Miller et al 48 showed that therapist empathy had a 0.82 correlation with improved drinking outcomes at 6-month follow-up. Empathy is thought to facilitate formation of a therapeutic alliance, defined by Connors et al 49 as "a collaborative relationship that consists of an emotional bond and shared attitudes regarding the tasks and goals of the treatment endeavor."…”
Section: Empathic Understanding Of the Patient's Situationmentioning
confidence: 99%